EVALUASI PROGRAM OPERASI PANGAN RIAU MAKMUR ( OPRM ) DI KABUPATEN PELALAWAN TAHUN 2010-2013 - Ulfa, Zamira; Ridwan, Muhammad (Universitas Riau, 2014)
Rice is the staple food of the people of Indonesia , especially in Riau , thus formingRice Production Enhancement Program in order to increase rice production in Riau , namelyRiau Makmur Food Operations program covering Improved Farming Index ( IP 100 - IP 200), Print new Rice and Rehabilitation Abandoned rice fields . This study aimed to evaluate theimplementation of the Programme of Food Operations Riau Makmur in the regency. Thisstudy focused on Pelalawan because considering the number of problems that occur in thefield , namely the realization of Food Operations Program Riau Makmur which is not inaccordance with the target . The research problem is how the human resources , infrastructure, program outcomes and the factors inhibiting Food Operations Riau ( OPRM ) . Based onthis background , the study aims to identify the implementation of Food Operations RiauMakmur ( OPRM ) and to identify the factors that affect the implementation of Operationinhibiting Food Riau Makmur ( OPRM ) .This research is descriptive in which researchers provide a description or picture ofthe phenomenon or social phenomena studied by describing the independent variablessystematically and accurately . Methods of data collection is done by observation andinterview . The results of this study indicate that in Pelalawan unsuccessful melaksanakaanFood Operations Program Riau Makmur ( OPRM ) seen from the indicators of humanresources , infrastructure dann inadequate results and factors - factors that influence thathuman resources are still low , inadequate infrastructure , lack of role of field workers andless active in the Coordination Node Pos district and village level .Keywords : Evaluation , OPRM , Pelalawan